ANALYSIS OF RICE BASED INCOME LOCAL WISDOM IN MANAGEMENT OF SWAMP LAND IN SOAK BATOK VILLAGE, INDRALAYA UTARA SUB-DISTRICT, OGAN ILIR DISTRICT - Eka Mulyana; Novayanti Novayanti; Dessy Adriani; Serly Novita Sari; Dimi Damayanti (Jurnal Scientia, 2023)
The purpose of this research were to: (1) identify local wisdom in the management of lowland swamps in Soak Batok Village, Indralaya Utara District, Ogan Ilir Regency, (2) to analyze the income of lebak swamp rice farming in Soak Batok Village, Indralaya Utara District, Ogan Ilir Regency, (3) analyzing the influence of local wisdom in the management of lowland swamps and other factors on the income of rice farming in Soak Batok Village, Indralaya Utara District, Ogan Ilir Regency. The method used in this research is descriptive exploratory method and survey method. Descriptive methods are used to describe or describe something based on actual conditions, such as conditions, circumstances, situations, events or activities. Furthermore, the survey method was used to obtain information on selling prices, production quantities, production costs, labor wages, and other sources of income from lebak swamp rice farmers in Soak Batok Village. This method is carried out by providing a list of questions (questionnaire) to the respondents and then conducting in-depth interviews with them. The data collection time was carried out from February 2021 to March 2021.